2007
DOI: 10.2298/ciceq0702068p
|View full text |Cite
|
Sign up to set email alerts
|

Anion effect on antimicrobial activity of metal complexes with benzimidazole derivative

Abstract: Chloride and nitrate of copper(II) and zinc(II) react with 1-(4-chlorobenzoyl)-2-methylbenzimidazole (L) to give complexes of the type ML2A2-nH2O (M=Cu or Zn; A=Cl- or NO3-; n=0, 1 or 2). Ligand and its complexes were evaluated for their in vitro antimicrobial activity against three Gram-positive bacterial strains: Bacillus sp., Staphylococcus aureus and Sarcina lutea, one Gram-negative isolate: Pseudomonas aeruginosa and one yeast: Saccharomyces cerevisiae. The compounds were more active against Gram-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The copper chelates system complex 4c was found to demonstrate higher inhibition (43 mm) at 10 ppm against P. aeruginosa compared with all other chelates, this may be attributed to the mobilized electron in the copper orbital as indicated by its magnetic property (Mwadham, 2013;Podunavac-Kuzmanovic, 2007;Patel et al, 2012). Presence of free electron in the Cu 2+ empowers its strong oxidative molecular activity for inhibitory ability on microorganisms as this re-emphasize the copper(II) ions as a key cofactor in a diverse array of biological oxidation-reduction reactions (Mwadham, 2013;Podunavac-Kuzmanovic, 2007;Jezowska, 2001;Jezowska et al, 1998;Solomon et al, 1996). …”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The copper chelates system complex 4c was found to demonstrate higher inhibition (43 mm) at 10 ppm against P. aeruginosa compared with all other chelates, this may be attributed to the mobilized electron in the copper orbital as indicated by its magnetic property (Mwadham, 2013;Podunavac-Kuzmanovic, 2007;Patel et al, 2012). Presence of free electron in the Cu 2+ empowers its strong oxidative molecular activity for inhibitory ability on microorganisms as this re-emphasize the copper(II) ions as a key cofactor in a diverse array of biological oxidation-reduction reactions (Mwadham, 2013;Podunavac-Kuzmanovic, 2007;Jezowska, 2001;Jezowska et al, 1998;Solomon et al, 1996). …”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Interestingly, metal complexes of 8-hydroxyquinoline as a primary ligand can exhibit biological activity (Noorulla and Sreenivasulu, 2011;Singh et al, 2010;Freeman, 1973;Che and Siu, 2010;Podunavac-Kuzmanovic and Cvetkovic, 2007) and an amino acid as a secondary ligand were significant as potential model for enzyme metal ions substrate complexes (Patel et al, 2012). Literature survey to the best of our knowledge showed that our newly synthesized compounds inhibit the standard test microorganisms favourably (Patil, et al, 2012;Eddie et al, 2010;Khalil et al, 2010;Gaurav et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The position and type of the substituents on the benzimidazole ring are responsible for the variety of biological activities. Many derivatives of benzimidazole are well known as antibacterial agents, as well as this class of compounds have been found to show antimicrobial activities against Gram-positive and Gramnegative bacteria, primarily because of the potential bio-activity of benzimidazole-based ligands [8][9][10][11][12][13][14][15][16][17][18][19]. So, the incorporation of the imidazole and benzimidazole nuclei is an important synthetic strategy in drug discovery.…”
mentioning
confidence: 99%
“…In view of the above and in continuation of our studies on inhibitory activities of benzimidazole derivatives [4][5][6][7], [11][12][13][14][15][16][17][18], as well as on correlation of molecular properties with activity, the objective of this investigation was to study the usefulness of QSAR in the prediction of the antibacterial activity of benzimidazole derivatives against Gram-negative bacteria Pseudomonas aeruginosa. The multiple linear regression (MLR) models have been developed as mathematical equations which relate chemical structure to the inhibitory activity.…”
mentioning
confidence: 99%
“…Biologically active benzimidazoles have been known for a long time and they can act as bacteriostats or bactericides [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The literature indicated that the benzimidazole nucleus is an essential part of many clinically useful chemotherapeutic agents.…”
mentioning
confidence: 99%